Predictive Risk Factors for Impaired Quality of Life in Middle-Aged Women with Urinary Incontinence - Son, Youn-Jung (Korean Continence Society, 2010)
PURPOSE: Urinary incontinence (UI) has substantial and important impacts on quality of life (QoL). The purpose of this study was to identify the associated risk factors of QoL in middle-aged women with UI. METHODS: The participants were 127 women aged 40-64 years who experienced UI. Data were collected from October to November, 2008 using a self-reported questionnaires. The data were analyzed through t-test, one-way ANOVA, Scheffe test, and multiple linear regression with SPSS ver. 16.0 program. RESULTS: The distribution of UI severity was mild 18.1%, moderate 40.2% and severe 41.7%. In univariate analysis, differences in the score for QoL according to participants' characteristics were statistically significant on the type of delivery, number of births and severity of UI. In multiple linear regression analysis after adjustment of other variables, the most powerful predictor of QoL is severity of UI. Number of births was also significant predictor. These two variables explained 25% of variance in QoL of women with UI. CONCLUSIONS: UI is highly prevalent and causes suffering and impaired QoL among middle-aged women, but it stands beyond our attention. The results of this study suggest that women with moderate to severe UI should be screened for QoL by health care providers regularly. Further research is needed to determine comprehensive factors including psychosocial factors predicting the QoL for incontinent women.